The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-46323-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternally perceived quality and pattern of fetal movements and late stillbirth

Abstract: We investigated fetal movement quality and pattern and association with late stillbirth in this multicentre case-control study. Cases (n = 164) had experienced a non-anomalous singleton late stillbirth. Controls (n = 569) were at a similar gestation with non-anomalous singleton ongoing pregnancy. Data on perceived fetal movements were collected via interviewer-administered questionnaire. We compared categorical fetal movement variables between cases and controls using multivariable logistic regression, adjusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Bradford et al ( 31 ) examined the association between fetal movements’ quality and pattern to late stillbirth in a case-control study. They concluded that changes in the fetal movement pattern such as a decrease in the strength and frequency of fetal movements and a fetal calmness during the night hours were more likely to be experienced from women with stillbirths ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bradford et al ( 31 ) examined the association between fetal movements’ quality and pattern to late stillbirth in a case-control study. They concluded that changes in the fetal movement pattern such as a decrease in the strength and frequency of fetal movements and a fetal calmness during the night hours were more likely to be experienced from women with stillbirths ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fetal movements (FMs) in pregnancy have long been used as an indicator of fetal wellbeing. A reduction in or absence of FMs may indicate fetal compromise or death [ 1 , 2 ]. The prevalence of women presenting with reduced FMs in pregnancy ranges from 4 to 23% across studies [ 3 5 ], with up to 55% of women experiencing a reduction in FMs in the days preceding an intrauterine death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another case-control study, it was found that women who reported increased strength of movements in the last 2 weeks had decreased risk of late stillbirth compared with those whose movements were unchanged [ 4 ]. Women who perceived their fetus to be quiet in the evening have an almost four-fold increased odds of late stillbirth [ 5 ]. Reduction of fetal movement also correlates with fetal hypoxia, fetal growth restriction, umbilical cord complications, being small for gestational age and long-term neurodevelopmental impairment [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women who perceived their fetus to be quiet in the evening have an almost four-fold increased odds of late stillbirth [ 5 ]. Reduction of fetal movement also correlates with fetal hypoxia, fetal growth restriction, umbilical cord complications, being small for gestational age and long-term neurodevelopmental impairment [ 5 , 6 , 7 , 8 , 9 ]. In addition to reduction of fetus movements, there is also a hypothesis that a sudden episode of excessive fetal activity indicates fetal compromise, for example, representing fetal seizures, which if it persists can lead to fetal death [ 10 ].…”
Section: Introductionmentioning
confidence: 99%